Structural and physicochemical characterization of modified starch from arrowhead tuber (Sagittaria sagittifolia L.) using tri-frequency power ultrasound - Husnain Raza; Kashif Ameer; Haile Ma; Qiufang Liang; Xiaofeng Ren (Ultrasonics Sonochemistry, 2021)
Sagittaria sagittifolia L. is a well-known plant, belongs to the Alismataceae family. Sonication can improve the functional properties of starch; hence, the aim of this study was to develop ultrasonically modified arrowhead starch (UMAS) using a sophisticated and eco-friendly tri-frequency power ultrasound (20/40/60 kHz) method at 300, 600, and 900 W for 15 and 30 min. Significant (p < 0.05) increases in swelling power, solubility, and water and oil holding capacities were achieved. FTIR spectroscopy corroborated the ordered, amorphous, and hydrated crystals of the sonicated samples. Increases in sonication frequency and power led to significant (p < 0.05) increases in onset gelatinization temperatures. Scanning electron microscopic analysis of sonicated samples showed superficial cracks and roughness on starch granules appeared in a sonication power-dependent manner compared with that of untreated sample. Overall, the ultrasonically-treated samples showed improved physicochemical properties, which could be useful for industrial applications.